Primary Diaphragmatic Dedifferentiated Liposarcoma in a Young Female Patient after Delivery - Shinya Sakata; Chieko Yoshida; Sho Saeki; Susumu Hirosako; Hidenori Ichiyasu; Hirotsugu Kohrogi (Case Reports in Oncological Medicine)
A 26-year-old woman was admitted with the chief complaint of chest pain. She had delivered her first child 9 months before admission. Computed tomography showed a bulky mass in her left chest, and histopathological analysis revealed it to be dedifferentiated liposarcoma. We initiated doxorubicin chemotherapy, and the tumor mass reduced. After that, we performed vascular embolization along with chemotherapy, but tumor size did not reduce. On the 160th day of illness, the patient died. This is the first report of a primary diaphragmatic dedifferentiated liposarcoma diagnosed after delivery. Establishment of a regimen of chemotherapy for bulky unresectable liposarcoma is necessary.